Special operations forces in the 21st century perspectives from the social sciences (Cass Military Studies, 2018)
This book sets out the major social scientific approaches to the study of Special Operations Forces. Despite consistent downsizing, over the past two decades the armed forces of the industrial democracies have seen a huge growth in Special Operations Forces (SOF). Through increasing numbers of personnel and more frequent deployments, SOF units have wielded considerable influence in conflicts around the world, with senior SOF officers having led major strategic operations. This increased presence and unprecedented expansion for SOF is largely a result of the 'new' kinds of conflicts that have emerged in the 21st century